The Role of Faith-inspired Health Care Providers in Sub-Saharan Africa and Public-Private Partnerships : Strengthening the Evidence for Faith-inspired Health Engagement in Africa, Volume 1 - Olivier, Jill (World Bank, Washington, DC, 2013)
This role of faith-inspired health care providers in sub-saharan Africa and public-private partnerships is comprised of a three volume series on strengthening the evidence for faith inspired engagement in health in sub-Saharan Africa. An increasing level of interest in the role of faith in development has generated much debate and dialogue at the international and national levels over the last decade. Despite difficulties in communication and differences in cultures within such debates, there has been a continued reaffirmation of the potential benefits that faith-inspired communities can bring towards efforts to achieve the millennium development goals (MDGs), especially in the areas of health. This series focuses on assessing the role and market share of faith-inspired providers and on assessing the extent to which they are involved in and benefit from public-private partnerships. The purpose of this series of three HNP discussion papers is to round up various analytical perspectives and emerging research on faith engagement in health in Africa from a range of researchers and practitioners from the north as well as the south. The series is structured into three volumes: a first volume on the role and market share of faith-inspired providers and public-private partnerships, a second on satisfaction and the comparative nature of faith-inspired health provision, and the third on mapping of faith inspired provision and the extent to which faith-inspired providers reach to the poor.